2020
DOI: 10.3389/fped.2020.00577
|View full text |Cite
|
Sign up to set email alerts
|

Complex Multisystem Phenotype With Immunodeficiency Associated With NBAS Mutations: Reports of Three Patients and Review of the Literature

Abstract: Objectives: Mutations in the neuroblastoma-amplified sequence (NBAS) gene were originally described in patients with skeletal dysplasia or isolated liver disease of variable severity. Subsequent publications reported a more complex phenotype. Among multisystemic clinical symptoms, we were particularly interested in the immunological consequences of the NBAS deficiency. Methods: Clinical and laboratory data of 3 patients ages 13, 6, and 5 in whom bi-allelic NBAS mutations had been detected via next-generation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Other authors showed how the aetiology of biallelic mutations in the NBAS gene resulted in recurrent episodes of acute liver failure, as shown in our study [4,6,27,28,30,31]. Nonetheless, these two mutations were not identified in any of these studies, thus indicating their significance in causing abnormal liver function and Fanconi syndrome in SOPH patients.…”
Section: Discussionmentioning
confidence: 46%
“…Other authors showed how the aetiology of biallelic mutations in the NBAS gene resulted in recurrent episodes of acute liver failure, as shown in our study [4,6,27,28,30,31]. Nonetheless, these two mutations were not identified in any of these studies, thus indicating their significance in causing abnormal liver function and Fanconi syndrome in SOPH patients.…”
Section: Discussionmentioning
confidence: 46%
“…We strived to perform a comparative analysis between the phenotypes of SOPH patients and carriers of the p. Arg1914His variant in the compound heterozygous state. In total, we have found the descriptions of 17 cases with compound heterozygosity in the available literature 6,10‐16 . Genetic variants other than p. Arg1914His in the NBAS gene included 1 missense, 7 nonsense, 4 frameshift, 3 splice‐site variants, and 2 long in‐frame deletions.…”
Section: Resultsmentioning
confidence: 99%
“…We strived to perform a comparative analysis between the phenotypes of SOPH patients and carriers of the p. Arg1914His variant in the compound heterozygous state. In total, we have found the descriptions of 17 cases with compound heterozygosity in the available literature 6,[10][11][12][13][14][15][16] . We did not find any specific traits regarding the cardiovascular, endocrinological, and the hematopoietic systems.…”
Section: Arg1914his Compound Phenotypementioning
confidence: 99%
“…В случаях сиблингов из 2 различных семейпациенты №3 и 4 и пациенты №5 и 6 -изначально при помощи метода NGS были обнаружены гетерозиготные мутации в соответствующих генах: в семье пациентов №3 и 4 -в гене DCLRE1C: NM_001033855: c.1478_1479delTT (p.Phe493*) и в семье пациентов №5 и 6 -в гене NBAS: NM_015909: c.5741G>A (p.Arg1914His) [20]. Клиническая и лабораторная картина сиблингов в первой семье соответствовала комбинированному иммунодефициту, во второй семье -иммунодефициту с проявлениями несовершенного остеогенеза.…”
Section: результаты исследованияunclassified